2020
DOI: 10.1007/s11244-020-01345-5
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Mixed Dyes in Aqueous Phase by MgAlTi and ZnAlTi Mixed Oxides

Abstract: This study reported the synthesis and evaluation of mixed metal oxides MgO/Al 2 O 3 -TiO 2 and ZnO/Al 2 O 3 -TiO 2 as heterogeneous photocatalysts for the potential degradation of a mixture of organic dyes such as methylene blue and methyl orange. First, hydrotalcites were synthesized by two different methods (conventional and microwave); then they were treated at 500 °C to obtain the corresponding Mg/Al-Ti and Zn/Al-Ti mixed metal oxides. The Layered Double Hydroxide (LDH) and the Mixed Metal Oxides were char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Furthermore, the apparent kinetics (Kapp) for the photodegradation of phenol were obtained by the Langmuir-Hinshelwood formalism, which applies for pseudo-first-order in the photodegradation of phenol. As shown in the graph of ln C/Co versus time (Figure 9) [54,55], the kapp values and half-life time for the reactions were also obtained, as reported in Table 2.…”
Section: Photocatalytic Evaluationmentioning
confidence: 76%
See 1 more Smart Citation
“…Furthermore, the apparent kinetics (Kapp) for the photodegradation of phenol were obtained by the Langmuir-Hinshelwood formalism, which applies for pseudo-first-order in the photodegradation of phenol. As shown in the graph of ln C/Co versus time (Figure 9) [54,55], the kapp values and half-life time for the reactions were also obtained, as reported in Table 2.…”
Section: Photocatalytic Evaluationmentioning
confidence: 76%
“…Furthermore, the apparent kinetics (K app ) for the photodegradation of phenol were obtained by the Langmuir-Hinshelwood formalism, which applies for pseudo-first-order in the photodegradation of phenol. As shown in the graph of ln C/Co versus time (Figure 9) [54,55], the k app values and half-life time for the reactions were also obtained, as reported in Table 2. When following the photodegradation of phenol with a UV-vis spectrophotometer, the following behavior was observed: the most active photocatalyst was the one that was treated at 600 °C, followed by the catalysts treated at 500 > 700 > 400 > 800 °C.…”
Section: Photocatalytic Evaluationmentioning
confidence: 81%
“…"In this same vein, a study has reported the synthesis and evaluation of the mixed metal oxides MgO/Al 2 O 3 -TiO 2 and ZnO/Al 2 O 3 -TiO 2 as heterogeneous photocatalysts for the photo degradation of a mixture of organic dyes such as methylene blue and methyl orange" [12]. Similar works but with different types of photocatalyst, mostly in the form of nanoparticles or composites have been reported in literature [13,14,15].…”
Section: Introductionmentioning
confidence: 84%